ln(x-2)+ln(2x+1)=6

Simple and best practice solution for ln(x-2)+ln(2x+1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x-2)+ln(2x+1)=6 equation:


Simplifying
ln(x + -2) + ln(2x + 1) = 6

Reorder the terms:
ln(-2 + x) + ln(2x + 1) = 6
(-2 * ln + x * ln) + ln(2x + 1) = 6
(-2ln + lnx) + ln(2x + 1) = 6

Reorder the terms:
-2ln + lnx + ln(1 + 2x) = 6
-2ln + lnx + (1 * ln + 2x * ln) = 6
-2ln + lnx + (1ln + 2lnx) = 6

Reorder the terms:
-2ln + 1ln + lnx + 2lnx = 6

Combine like terms: -2ln + 1ln = -1ln
-1ln + lnx + 2lnx = 6

Combine like terms: lnx + 2lnx = 3lnx
-1ln + 3lnx = 6

Solving
-1ln + 3lnx = 6

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-6 + -1ln + 3lnx = 6 + -6

Combine like terms: 6 + -6 = 0
-6 + -1ln + 3lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 13-3(x+7)=15 | | ln(x-2)+(2x+1)=6 | | -(1+7x)-6(-7-x)=46 | | -10(-8x+9)-8x=72x-90 | | 9xn=0.25 | | 4x+-y=-2 | | 9x^2+11=-17 | | 9=d*21 | | 849.50+23.50h=685 | | 4(y-2)=44 | | 1+0.2+7x=470 | | 2(x-3y)-4(x+2y)= | | 2000x=302 | | 6(8)-(3(8)+8)=16 | | 21/4-1+3=x | | 1-28=0.025(32+x) | | 7.4=1.8y-16 | | 9x^2+11=-7 | | 2(x+8)=5x+3-3x+13 | | 0.5x+0.25(50-x)=170 | | 2(9-4)+7=x | | 120+10h=310 | | 252=25x+3x | | (13b-2)-6(2b+4)=-3 | | 3x+150=6(20+x) | | 5+.50m=12 | | xsquared-6x=0 | | -3*1.666666667-7= | | Y-9+6y=30 | | 5+.50m=3000 | | 53151m-12412m= | | 1800+50w=3000 |

Equations solver categories